Low incidence of alpha-1-antitrypsin deficiency in Iranian patients with neonatal cholestasis - Motamed, Farzaneh; Mehrabani, Sanaz; Monajemzadeh, Maryam; Ashtiani, Mohammad Taghi Haghi; Hosseinverdi, Sima; Houshmand, Masoud; Aryani, Omid; Najafi, Mehri; Farahmand, Fatemeh; Kiani, Mohammad Ali; Khodadad, Ahmad; Fallahi, Gholam Hossein; et al. (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: There is little data concerning the incidence of alpha-1-antitrypsin”(AAT) deficiency, the most common genetic cause of liver disease, among children with neonatal cholestasis in Iran. Thus, this study was performed to analyze AAT deficiency in this group of patients. Materials and Methods: DNA samples from patients with neonatal cholestasis were investigated for Pi S and Pi Z alleles, using polymerase chain reaction–restriction fragment length polymorphism. Results: Thirty patients with neonatal cholestasis were enrolled. Among those who underwent biopsies, the results revealed neonatal hepatitis in 19, bile duct paucity in 1, steatohepatitis in 1, bile duct proliferation in 1, cirrhosis in 2, fibrosis in 2, and extrahepatic biliary atresia in 1 patient. No mutant allele was found in any patient. Conclusion: The incidence of AAT deficiency is very low in Iran; therefore, screening for AAT is not recommended for patients with neonatal cholestasis in Iran.